PROFIL KETERAMPILAN PROSES SAINS DAN SIKAP ILMIAH SISWA DI SMP SATU ATAP PULAU TUNDA - Aditya Rahman (PGSD Universitas Negeri Medan, 2017)
This research aims in descripting Science Process Competence (KPS) and student scientific behavior at SMP I Atap Pulau Tunda, Tirtayasa Region, Serang Regency. This research was an introduction research /observation to determine the study method or model that can elevate KPS and student scientific attitude. The research sample was students of SMP I Atap Pulau Tunda selected by purposive sampling. Data was collected from KPS test, observation sheets of students scientific behavior during learning process, interview sheets, and learning rank by the teacher. This research result shows that the Science Process Competence and the scientific behavior of the students were still low. Some of the reasons were the learning process was still ‘teacher centered’, the teacher knowledge related to KPS and the scientific behavior was still not adequate, and the training experience was still not maximum. Trainings given to teacher related to learning method and model, seminars about KPS and scientific behavior, and facilitation given by of the headmaster and the government are hopefully can elevate Science Process Competence and the scientific behavior at SMP I Atap Pulau Tunda. Key Words: Science Process Competence, Scientific Behavior, and Science